Diardi Pisponi Benin has a buyer, Sayyid Sadiq - علی, هاودین کامل; حمەیوسف, عطا احمەلاو (Sulaimani Journal for Humanities, 2025)
Analysis and evaluation of the scenery and beauty of the city that is of great importance to the architects and architects, and its reflection in the building Map, design and planning of residential neighborhoods, buildings and streets of the city, along all sides of the city must be protected Look at the credibility, for example, the organization of land use, color and architectural design, billboards, and numbers Construction and architecture details and agreement between shops and commercial shops for the market. . . . . . . . . ، even through this path is possible Guaranteeing the self-destruction of the city and the liberation of the city from the resources of Al-Basra. Said Sadiq city, a city belonging to Sulaimaniyah governorate in Kurdistan region, research sources and The reasons for the appearance in the city, due to the increase in the number of dwellings, prisoners, residential units and their expansion in the city, وكذلك ازداد الظاهرة day after day. The results of the study show that all the jewels of Basra are located in the city center and most of them are located in the market center of the city Obviously, the sources of this type of waste are diverse and some of them are defects in the design and architectural planning of the city and lack of organization Shapes of land use, types and sizes of advertisements, electricity lines and health distribution. The main reason for the destruction of Basra in this city goes back to Ayub and the lack of architectural planning in the structure For the city and economic factors and deprivation of the head of the municipality and the administrative authority of the city. The study describes the layout of the streets, shops and commercial establishments in the market Provide beautiful and civilian views of the city and implementation of the new civilizational city. The study emphasizes the importance of rehabilitation Organization of related education by issuing permits, books, size and posting of billboards, and smoke control using colors Construction site, in front of buildings, houses and commercial buildings.